Encapsulación por inclusión molecular del aceite esencial de naranja: Efecto del método de secado en las características físicas, químicas, estructurales y estabilidad - Huaman Lopez, Malory (2024)
Previous investigations suggested the orange essential oil as antimicrobial and natural antioxidant; however, the high volatility and sensibility due to extern factors are imitating its applications. Thus, the encapsulation is an ideal alternative of protection for essentials oils and the molecular inclusion has greater advantages compared to others, but the drying method and temperature can influence its characteristics and stability. Therefore, the orange essential oil was microencapsulated into beta-cyclodextrin (β-CD), and was evaluated the effect of drying by stove, lyophilization and atomization (160, 180 and 200 °C) on humidity, water activity, encapsulation efficiency, yield, and stability (82% relative humidity for 36 days). The microparticles were analyzed by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscope (SEM). The best drying method was lyophilization achieved an encapsulation efficiency of 97,35%, humidity 1,76%, water activity 0,54, and low hygroscopicity 0,20%. The results by FTIR found the formation and loss of some bonds between orange essential oil and beta-cyclodextrin, probably by effect of temperature. The lyophilized microparticles presented best stability with final efficiency of 52,53% with low humidity and water activity. This study makes it possible to establish the best drying method in cases of molecular inclusion, which may be useful in future applications when developing products.